TEACHERS’ STRATEGIES FOR DEALING WITH LGBTQI LEARNERS AT SECONDARY SCHOOLS IN THE NONGOMA CIRCUIT - Londiwe Patience Njapha,; Primrose Ntombenhle Khumalo,; Alan Bhekisisa Buthelezi,; Oluwatoyin Ayodele Ajani, (International Journal of Innovative Technologies in Social Science, 2024)
This study examined secondary school teachers' perceptions of LGBTQI learners within the Nongoma Circuit, focusing on the interactions between teachers and LGBTQI students and identifying effective engagement strategies. Adopting a phenomenological philosophy, the research aimed to understand the lived experiences and meanings of teachers' perspectives. A qualitative approach was employed to provide flexibility in exploring these experiences. The study utilised a phenomenological design to uncover nuanced insights into teachers' attitudes. The sample comprised five Life Orientation educators from secondary schools in the Nongoma Circuit, selected through purposive sampling to ensure rich, relevant data. Data were collected via semi-structured interviews and analysed thematically. To ensure the trustworthiness of the findings, the study addressed credibility, transferability, dependability, and confirmability. Social constructionism served as the theoretical framework, offering a sociological perspective on human behaviour and interactions. Findings indicated a range of attitudes towards LGBTQI learners, from positive acceptance to negative biases. The study highlighted the need for enhanced training and support for educators to create inclusive and secure educational environments for all students, regardless of sexual orientation or gender identity. Thematic analysis revealed diverse viewpoints, underscoring the importance of targeted teacher training and policy reviews to foster empathetic and inclusive learning spaces. The results suggest crucial steps towards improving secondary school environments by addressing LGBTQI issues comprehensively within teacher training programs and school policies.